Pengembangan LKPD berbasis Problem Based Learning Pada Materi Alkanal dan Alkanon untuk Kelas XII SMA/MA - Jasperina Jasperina; Suryelita Suryelita (Edukimia, 2019)
Alkanale and alkanone are parts of the carbon compounds taught on the second semester of 3rd grade Senior High School. But the implementation was compressed in the first semester and consequently, learning process isn’t optimal. The purposes of this research are to develop a Problem Based Learning Student Worksheet and determine its validity and practicality. This research using 4-D models; define, design, and develop but disseminate stage isn’t done. Used instruments are validity and practicality questionnaire given to chemistry lecturers at FMIPA UNP, chemistry teachers and students at SMAN 2 Bukittinggi. The result was analysed by Kappa Cohen Formula. Based on the result, validity and teacher’s practicality of developed worksheet gain a very high category with each 0,83 and 0,92 point of kappa moment, and student’s practicality obtain 0,75 point of kappa moment, which is a high practicality category.